The influence of the quantitative and specific composition of the microbiota of poultry houses on the prevalence of respiratory diseases and their prevention - Smirnov S.L. (BIO Web of Conferences)
The scientific article presents the results of research for 2023, conducted in poultry farms in the Kostroma region, to study the influence of the quantitative and specific microbial composition of the air on the prevalence of respiratory diseases in poultry of egg and meat production. In the course of the conducted research, it was found that the air of most poultry houses of poultry farms is polluted with bioaerosols containing a large amount of dust and microorganisms. The inhalation of such bioaerosol by a bird provokes the occurrence and development of an inflammatory process in the respiratory organs. An analysis of veterinary reporting data showed that in poultry farms, in the structure of diseases of non-infectious etiology, diseases of the digestive system account for 31%, respiratory diseases 29%, liver 11%, kidneys 9%. High load on poultry houses, limited areas, high planting density of broiler chickens, and technological disruptions are factors that lead to various diseases, primarily respiratory diseases, which dramatically reduce poultry productivity and safety.